Modeling and simulation of matrix converter using space vector control algorithm - Erdem, E; Tatar, Y; Sünter, S (Ieee, 2005)
In this work, Matlab/Simulink modeling and simulation of the three - phase matrix converter feeding a passive RL load have been performed using the space vector control algorithm. The model has been designed to support real time implementation with a simulation supported DSP control board. The algorithm uses a simpler method than the other control algorithms to control the input power factor. In addition, it has lower switching loses and easy implementation. Simulation has been implemented for various output frequencies at unity input power factor. The simulation results of input current, output voltage and current waveforms are presented with their spectra.
International Conference on Computer as a Tool (EUROCON 2005) -- NOV 21-24, 2005 -- Belgrade, SERBIA MONTENEG
Keywords: matrix converter; space vector control algorithm